(untitled) (Pulse, 2014)
A 28 year old male patient of psoriasis was admitted in a tertiary care hospital of Bangladesh with typical skin lesions for 18 years, nail changes for 16 years, arthritis for 12 years and eye changes for 3 years. In addition he had other rare extra articular complications like severe aortic stenosis, moderate aortic regurgitation and mild mitral regurgitation. He had a positive family history of psoriasis. HLAB27 is positive and X-ray of hands and feet showed classical findings of psoriatic arthritis. We presented the case to show the early age of onset, severity of the disease with rapid progression and multiple extra articular complications. DOI: http://dx.doi.org/10.3329/pulse.v5i2.20266 Pulse Vol.5 July 2011 p.48-53